The effects of grate clinker cooler on specific energy consumption and emissions of a rotary kiln in cement industry. (2015) - Atmaca, Adem; YumrutaÅ, Recep
Cement production is considered one of the major contributors to environmental pollution and requires implementation of more efficient sustainability practices. This study focuses on grate clinker coolers (GCCs), which are used to recover heat from hot clinker produced in rotary kiln (RK). The effects of mass flow rate and temperature of cooling air on the performance of the GCC and RK are investigated. It is found that the first- and second-law efficiencies of the RK can be increased by 2.62 and 2.13%, respectively, by increasing the mass flow rate of cooling air by 13% in GCC. The SEC for clinker production is determined to be 3121.8 kJ/kg clinker. Changing the operating conditions in GCC provides 3.64% reduction in energy consumption corresponding to a saving of 113.6 kJ per kg of clinker production. The applications prevent the emission of 674.66 tons of CO2 per year to the atmosphere.